COVID-19 AND NEW ONSET HYPERTENSION. (June 2022) - Shalaeva, Evgeniya; Shamsutdinova, Maksuda; Shadmanov, Alisher; Boymuradov, Shukhrat; Azizova, Feruza; Allaberganov, Dilshod; Saner, Hugo; Messerli, Franz
Abstract : Objective: COVID-19 has been identified as a possible risk factor for hypertension. It may be associated with new onset hypertension or aggravate pre-existing hypertension. The objective of the study was to evaluate systolic (SBP) and diastolic blood pressure (DBP) pattern in COVID-19 patients discharged from the hospital and followed for over 3 months. Design and method: This is a prospective single-center observational cohort study of 1442 hospitalized COVID-19 patients including 259 ICU patients followed over 3-months (52.4 ± 12.3 years, 49.8% male) in Uzbekistan January-June 2021. Patients were subclassified according to JNC 8 hypertension stages. For patients who died, the last confirmed BP was used. Results: In the whole cohort, all-cause mortality was 137 (9.5%). At 3-months in ospitalisat patients (no ICU treatment), mean SBP was raised on 7.4 mmHg, DBP 5.7 mmHg compared to the 1st day of admission due to COVID-19, in ICU patients SBP increased by 12.5 mmHg and DBP 7.2 9 mmHg (Table 1). The prevalence of hypertension in the whole cohort subclassified according to JNC8 criteria is presented in Table 2. In the whole cohort at the baseline, according to JNC8, hypertension was detected in 713 (49.4) patients, and by 3-months follow-up new incidence of hypertension was observed in 254 (17.6%) patients. 483 (65%) patients with diagnosed hypertension at the baseline were required to increase the doses of antihypertensive medications after discharge during 3-months follow-up. Conclusions: COVID-19 necessitating ospitalisation is a powerful risk factor for new onset hypertension or for aggravating pre-existing hypertension.